Bodies : exploring fluid boundaries - Longhurst, Robyn, 1962- (Critical geographies, 2001)
"Geography has recently seen something of a 'body craze'. The politics that surround bodies and spaces are increasingly being held up to scrutiny. Despite this, the 'leaky', 'messy' zones between the inside and outside of bodies and their resulting spatial relationships, remain largely unexamined in the discipline." "This book revolves around three case studies - pregnant bodies in public places, men's bodies in domestic toilets and bathrooms, managers' bodies in Central Business Districts. The pregnant body threatens to expel matter from inside. It is often described as 'ugly' or as 'matter out of place'. Geographers have ignored men's bodies in domestic toilets and bathrooms because these places are abject sights/sites where bodily boundaries are broken and then made solid again. Female and male managers in Central Business Districts wear tailored, dark coloured business suits, that give the appearance of a body which is impervious to leakage or penetration." "The case studies illustrate that bodies and spaces are socially constructed and yet have an undeniable materiality and fluidity. Ignoring the everyday materiality of bodies that 'leak' and 'seep' is not a harmless omission, rather it contains a political imperative that helps keep masculinism intact."